24 Protecting the Heart at a Distance: Exosomes for nano-sized Cardioprotection. (19th January 2014) - Vicencio, J M; Boi-Doku, C; Das, D; Sivaraman, V; Kearney, J; Hall, A R; Arjun, S; Zheng, Y; Yellon, D M; Davidson, S M
Abstract : Rationale: Preconditioning is widely known to protect cardiomyocytes from reperfusion-induced cell death by activation of several pro-survival transductional pathways. The fact that preconditioning can be achieved remotely (Remote Ischaemic Preconditioning, RIPC) means that humoral factors are released from ischaemic limbs into the circulation carrying a pro-survival message. Exosomes are circulating nano-sized vesicles that mediate inter-cellular communication by carrying diverse proteins and RNA molecules. Here we studied the role of exosomes in mediating RIPC. Methods and Results: We isolated exosomes from plasma of rats or humans subjected to RIPC. We characterised control or RIPC exosomes by electron microscopy, flow cytometry, western blot and nano-particle tracking analysis. Exosome concentration increased dramatically after RIPC in humans (from 3.5 ± 0.3x10 8 to 1.1 ± 0.3x10 9 exosomes/ml plasma; p < 0.01, n = 6), and administration of purified exosomes protected the heart from infarct in different settings including an in vivo rat model (vehicle: 47.4 ± 4.7; RIPC-Exosomes: 20.5 ± 3.9%Infarct/AAR; p < 0.01), ex vivo Langendorff (vehicle: 35.2 ± 3.3; RIPC-Exosomes: 21.2 ± 2.5% Infarct/AAR; p < 0.01), and in vitro hypoxia-reoxygenation of cardiomyocytes (43 ± 7% protection from death, p < 0.01). RIPC-Exosomes triggered rapid ERK phosphorylation (3.9 ± 0.1 fold over vehicle), and inhibition of upstream PI3K or MEK abolished ERK activation and inhibited cardioprotection. Conclusions: We demonstrate that RIPC dramatically increases the concentration of exosomes in the circulation. Exosomes acutely activate pro-survival kinases that rapidly prepare the heart against ischemia-reperfusion injury. Exosomes represent a novel agent with the potential to be an endogenous, non-immunogenic and multi-signalling tool for cardioprotection.